A study of entrepreneurial competencies of post graduate students in agriculture - MODAK, SATARUPA; PATEL, MEENA C; PAL, P K; DAS, LITAN; NAIN, M S (The Indian Journal of Agricultural Sciences, 2018)
Entrepreneurial competence being underlying characteristic of a person leads to effective or superior performance in a job. The study explored the level of entrepreneurial competence and its relationship with socio-personal characteristics of Post-Graduate students of Anand Agricultural University (Gujarat). The 150 postgraduate students were selected on proportionate random sampling basis. To measure entrepreneurship competency level, the indicators advocated by Entrepreneurship Development Institute of India were used. The study revealed that majority (92.00%) of the postgraduate students possessed moderate level of entrepreneurial competency. Among different component traits of entrepreneurial competency, information seeking behaviour, concern for high quality work and efficiency orientation were important. Socio-personal characters like knowledge of different languages, fathers’ education and risk orientation had positive impact and academic performance and agricultural business anxiety had negative impact on possession of entrepreneurial competency.